The development of jumping ability in young basketball players 12-13 years old - U. A. Farmonov (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2021)
To increase the level of jumping ability (high-speed strength abilities), a depth jump training program has been developed, taking into account technical and tactical actions in the game "Basketball". Classes in the basketball section are nothing more than a well-organized and well-thought-out system in which the qualitative and quantitative characteristics in the preparation of children correspond to both the general tasks of physical education and age-specific ones. Jumping like motor quality, refers to the speed-power abilities of a person. An indicator of a significant development of speed-strength training and, as a consequence, an increase in the quality of technical and tactical actions is a good jump